Perivascular adipose tissue and vascular disease. (February 2011) - Britton, Kathryn A; Fox, Caroline S
Perivascular adipose tissue is a local deposit of adipose tissue surrounding the vasculature. Perivascular adipose tissue is present throughout the body and has been shown to have a local effect on blood vessels. The influence of perivascular adipose tissue on the vasculature changes with increasing adiposity. This article describes the anatomy and pathophysiology of perivascular adipose tissue and the experimental evidence supporting its local adverse effect on the vasculature. Methods for quantifying perivascular adipose tissue in free-living populations will be described. Finally, the epidemiological literature demonstrating an association between perivascular adipose tissue and cardiometabolic disease will be explored.